Promoting medical student research in Nepal - Shanker, PR (Janaki Medical College Journal of Medical Science, 2014)
DOI: http://dx.doi.org/10.3126/jmcjms.v2i1.11388 Janaki Medical College Journal of Medical Sciences (2014) Vol. 2 (1): 1-3